ChemInform Abstract: Regio‐, Diastereo‐, and Enantioselective Nitroso‐Diels—Alder Reaction of 1, 3‐Diene‐1‐carbamates Catalyzed by Chiral Phosphoric Acids. Issue 10 (February 2016) - Pous, Jonathan; Courant, Thibaut; Bernadat, Guillaume; Iorga, Bogdan I.; Blanchard, Florent; Masson, Geraldine
Abstract: A series of cis‐3, 6‐disubstituted dihydro‐1, 2‐oxazines (III) is readily prepared by enantioselective nitroso‐Diels—Alder reaction of carbamate‐dienes (I) with nitrosoarenes (II) in the presence of chiral phosphoric acid BTIPA as a catalyst.